Pemikiran Potensial Ancaman Perang Siber di Indonesia: Suatu Kajian Strategi Pertahanan - Darumaya, Binar Arfa; Maarif, Syamsul; Toruan, Toruan; Swastanto, Yoedhi (Jurnal Keamanan Nasional, 2023)
The information technology revolution has changed the threat map into a more complex space. Cyberspace has become an unlimited platform for cyber activities conducted by various domestic, regional, and international actors. While some people in the world utilize advances in information technology for positive activities, others use it to present threats. This research analyses the State’s perspective on cyber threats, particularly in the context of cyber warfare, in line with Indonesia’s State defense doctrine that classifies threats into three forms: military, non-military, and hybrid. The research method used is qualitative. The research results are expected to provide a clear picture of the nature of the cyber war threat in Indonesia and the government’s strategy in dealing with it. Thus, it is expected that there will be synergy between the role of the TNI as the main component of national defense and related ministries/agencies in developing strategies and implementing the national defense system to face the threat of cyber warfare.